Perbanyakan Vanili (Vanilla Planifolia Andrews.) Dengan Penambahan Kinetin Melalui Teknik Kultur Jaringan Efek - Sarita, Rahma; Erawati, Dyah Nuning; Taufika, Ramadhan; Triwidiarto, Cherry; Cahyaningrum, Descha Giatri (Agropross : National Conference Proceedings of Agriculture, 2022)
The development of vanilla seeds through tissue culture techniques with the addition of growth regulator kinetin aims to increase the success of shoot formation and growth of vanilla explants. The research was carried out from February to June 2021 at the Tissue Culture Laboratory Politeknik Negeri Jember. The research method used a single factor Completely Randomized Design (CRD) with 4 treatments which were repeated 5 times. The treatment was the addition of kinetin to Murashige-Skoog (MS) media with a concentration of 0, 1, 2, 3 mg/L. Data analysis used analysis of variance followed by a 5% or 1% BNT test. The results of the analysis showed that the addition of kinetin affected the initial germination time of vanilla explants with the fastest time being 13-17 days after inoculation at a kinetin concentration of 1-3 mg/L. The kinetin concentration of 3 mg/L also affected the wet weight of vanilla explants aged 8 weeks after inoculation with the highest average of 2.62 grams per explant. However, the addition of kinetin did not affect root length, root number and shoot length until the vanilla explants were 8 weeks old after inoculation. .